Fluorescein angiographic findings and Behcet's disease ocular attack score 24 (BOS24) as prognostic factors for visual outcome in patients with ocular Behcet's disease - Narumon Keorochana; Nathamon Homchampa; Sritatath Vongkulsiri; Raveewan Choontanom (International Journal of Retina and Vitreous, 2021)
Abstract Purpose To determine the application of fluorescein angiographic (FA) findings and Behcet’s disease ocular attack score 24 (BOS24) scoring system in predicting poor visual outcome in patients with ocular Behcet’s disease. Study design Retrospective cohort study. Methods We included 73 eyes of 38 patients with ocular Behcet’s disease who underwent FA and reviewed FA images, anterior chamber cells, vitreous opacity, retinal and optic disc lesions, which are parameters in BOS24. The correlation between FA findings, BOS24, and visual acuity was assessed. Results Optic disc hyperfluoresence (74%), diffuse posterior pole leakage (52%) and diffuse peripheral leakage (52%) were the three most common findings. Common complications were peripheral capillary nonperfusion (29%), arterial narrowing (22%), and macular ischemia (19%). BOS24 scores of ≥ 6 (p < 0.0001), arterial narrowing (p < 0.0001), and severe posterior pole leakage (p = 0.004) were significantly associated with poor visual outcome. Combining significant FA findings: arterial narrowing and severe posterior pole leakage, to BOS24 ≥ 6 results in an increased relative risk of developing poor visual acuity from 7.30 to 10.43 and 1.89 to 2.02 respectively. Conclusion Fluorescein angiography is an important investigation for predicting poor visual outcome. BOS24 may be a useful alternative when fluorescein angiographic is unavailable.